Molecular and Cellular Mechanisms of Immunosenescence: Modulation Through Interventions and Lifestyle Changes - Luca Pangrazzi; Andreas Meryk (Biology)
Immunosenescence, the age-related decline in immune function, is a complex biological process with profound implications for health and longevity. This phenomenon, characterized by alterations in both innate and adaptive immunity, increases susceptibility to infections, reduces vaccine efficacy, and contributes to the development of age-related diseases. At the cellular level, immunosenescence manifests as decreased production of naive T and B cells, accumulation of memory and senescent cells, thymic involution, and dysregulated cytokine production. Recent advances in molecular biology have shed light on the underlying mechanisms of immunosenescence, including telomere attrition, epigenetic alterations, mitochondrial dysfunction, and changes in key signaling pathways such as NF-κB and mTOR. These molecular changes lead to functional impairments in various immune cell types, altering their proliferative capacity, differentiation, and effector functions. Emerging research suggests that lifestyle factors may modulate the rate and extent of immunosenescence at both cellular and molecular levels. Physical activity, nutrition, stress management, and sleep patterns have been shown to influence immune cell function, inflammatory markers, and oxidative stress in older adults. This review provides a comprehensive analysis of the molecular and cellular mechanisms underlying immunosenescence and explores how lifestyle interventions may impact these processes. We will examine the current understanding of immunosenescence at the genomic, epigenomic, and proteomic levels, and discuss how various lifestyle factors can potentially mitigate or partially reverse aspects of immune aging. By integrating recent findings from immunology, gerontology, and molecular biology, we aim to elucidate the intricate interplay between lifestyle and immune aging at the molecular level, potentially informing future strategies for maintaining immune competence in aging populations.